Impact of Financial Literacy on Investment Behavior and Consumption Behaviour of Middle-Class Families in Karnataka, India - et al., Dr. Sangeetha R (International Journal of Advanced Science and Technology, 2019)
Financial Literacy is an inevitable parameter in the current competitive society. The process of financial literacy is to make people aware about safe savings and other investment products available. This improved awareness will lead to better financial behaviour in terms of saving, budgeting and availing the credit wisely at cheaper cost. In tune with that, an attempt has been made in this paper to measure the impact of financial literacy on investment behavior and consumption behavior of middle-class families in Karnataka. Structured questionnaire is used to collect the data from 444 respondents. Stratified random sampling method is adopted.Confirmatory factor analysis is used to verify the model, and hypothesized relation is tested by applying the Structural Equation Model (SEM) to find the goodness of fit. The study resulted in that financial literacy has an impact on investment behavior and consumption behavior of the middle-class families in Karnataka. However, investment behavior is not influencing the consumption behavior of an individual and vice versa.